EXPLORING THE ACCEPTANCE OF PEER-TO-PEER LENDING: A MAQASID SHARIAH PERSPECTIVE THROUGH THE TECHNOLOGY ACCEPTANCE MODEL - Permatasari, Ditya; Nawirah, Nawirah; Sartika, Farahiyah; Setiani, Setiani (Faculty of Economics Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
This study applies the Technology Acceptance Model (TAM) to assess the adoption of peer-to-peer (P2P) lending by Micro, Small, and Medium Enterprises (MSMEs) in Malang, examining its influence on performance and business growth. Primary data were gathered via questionnaires completed by 192 MSME respondents utilizing P2P lending services. A snowball sampling technique was employed, and the data were analyzed using both descriptive and inferential statistical methods, with structural equation modeling based on Partial Least Squares (PLS). The findings indicate that Perceived Ease of Use exerts a significant positive effect on Perceived Usefulness, and similarly, Perceived Ease of Use positively influences Behavioral Intention to Use. Moreover, Perceived Usefulness significantly enhances Behavioral Intention to Use, which, in turn, positively affects Actual System Use. This research expands the TAM framework within the domain of Islamic financing for MSMEs, emphasizing the role of maqasid sharia in P2P lending. Key principles such as adherence to sharia-compliant transactions, the use of Islamic contracts, transparency, and ethical conduct in financial dealings are central to this framework. The study makes a significant contribution to the literature by illustrating how P2P lending technology, when integrated with sharia principles, can foster the growth and sustainability of MSMEs